Accounting information and stock price changes in Nepalese hydropower companies (Nepalese Journal of Management Research, 2023)
The study aimed to examine the relationship between accounting information (earnings per share, dividend per share and book value per share) on stock price changes (volatility) in Nepalese hydro power companies. It examined the impact of dividend per share, earnings per share and book value per share on stock price changes. Out of the 51 hydropower companies listed in Nepal Stock Exchange, Butwal Power Company Limited (BPC) and Chilime Hydro Power Company Limited (CHPC) were randomly selected for the study. The study period was covered 2073/2074 to 2078/2079 and data collected through the annual reports as well as data based on the Nepal Stock Exchange. Market value per share (MVPS) was taken as dependent variable and earnings per share (EPS), dividend per share (DPS) and book value per share (BVPS) as independent variables. Multiple regression analyses was used to identify the impact of accounting information on share price changes. A positive relation was found between EPS and MVPS in both companies. However DPS and BVPS showed mixed relationship (negative and positive) with MVPS of BPC and CHPC. The EPS of BPC found positive impact on MVPS. However DPS revealed negative impact on MVPS of both companies.